Information services to tenant companies in technology parks : Australia and Thailand. - Premkamolnetr, Nongyao (Curtin University, 1998)
This thesis investigates the most appropriate and effective ways in which a university library can interact with tenant companies and the staff in a technology park. Tenant company staff members in five Australian Technology Parks were surveyed about their information needs, information use, and information seeking behaviour as well as their attitudes towards university libraries which offered services to them. Three of the five Australian Technology Parks had formal relationships with universities and their libraries. The librarians of these universities were interviewed on their attitudes towards the provision of information services to the technology park community, as well as the information services they offered to this group of clients.The research results indicated that most of the respondents who were engaged in R&D areas accessed university libraries' collections for technical information and valued their services and the professional help of the librarians, whereas those in other areas, particularly marketing and sales, did not place as high a value on these services. One striking finding from the research was that the respondents in the latter group use the Internet as their preferred first source of information, not informal personal contact as been expected and indicated in previous studies. A contributing factor to low use of the university libraries was poor promotion of library services.A major objective of the research was to obtain information on the relevance of the Australian data to developing and offering services to tenants in a new technology park in Thailand. Results drawn from the Australian data was used to form a model for the interaction between university libraries and tenant company staff in Thai technology parks. The model was tested through interviews with Thai sample group and was then fine-tuned to meet Thai economic and social conditions prior to proposing it for use in Thailand.This research indicated that many aspects of Thai university libraries need to be adjusted in order to successfully provide effective information services to the technology park community. These include clearly defining library policies towards the tenants, increasing and improving avenues of access to library services, improving library performance and services, increasing promotion and marketing, supporting personnel development policies, and creating partnerships with other organisations.